The Role of Nursing Management in Building a Sustainable Patient Safety Culture - Sontina Saragih; Kalvin Ginting (Journal of Innovative and Creativity, 2026)
The study purpose was to examine the role of nursing management in building and sustaining a patient safety culture (PSC) within healthcare organizations. Given the increasing emphasis on safety as a key component of healthcare quality, understanding how leadership behaviors and organizational factors contribute to sustainable PSC is essential. This review aimed to synthesize recent evidence on nursing leadership approaches, sustainability mechanisms, and the challenges associated with maintaining long-term patient safety practices. Materials and methods. This study employed a systematic literature review design guided by the PRISMA framework. Databases including PubMed, Scopus, CINAHL, Web of Science, and ScienceDirect were searched for articles published between 2015 and 2025 using keywords such as “nursing management,” “patient safety culture,” “leadership,” and “sustainability.” A total of 26 peer-reviewed studies met the inclusion criteria. Data were extracted and analyzed thematically under four key domains: leadership styles, organizational support, sustainability strategies, and implementation barriers. Results. The findings revealed that transformational and participative leadership styles have the most substantial impact on developing and sustaining PSC. Organizational support systems—such as effective communication channels, non-punitive reporting structures, and ongoing leadership training—were found to reinforce safety behaviors and ensure cultural continuity. Barriers included limited resources, inconsistent leadership engagement, and high staff turnover. Conclusions. Nursing management serves as the cornerstone of a sustainable PSC. Effective leadership behaviors, when supported by institutional policies and adequate resources, drive organizations toward proactive and generative safety cultures. Sustainable safety outcomes depend on leadership constancy, staff empowerment, and systemic alignment across all levels of care.